2020
DOI: 10.30516/bilgesci.680500
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Rose Processing Wastewater By Sunlight/TiO2 Photocatalysis Process

Abstract: The objective of this study was to investigate the photocatalytic treatment of rose processing wastewater by using sunlight and TiO 2 . Rose processing wastewater contains high concentrations of chemical oxygen demand, high amount of solid matters and dark color. The effect of various operating conditions such as irradiation time, catalyst loading and pH on COD and color removal were determined. The highest color removal and COD removal was found to be 51.7 % and 15.7%, respectively with 2 g/L TiO2 catalyst do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Ultrasound could be considered an alternative method that enables and accelerates to degrade of high organic strength wastewater for the first time combined with photocatalyst and UV irradiation to treat PSWW and this is consistent with work done by Abdelhay et al, (2020) reported that the removal efficiency of COD from PSWW continued to increase during the sonication time (180 min). Çancı and Kılıç (2020) declared that the COD removal rate from rose processing wastewater decreased with increased reaction time due to the formation of colored intermediates as a result of oxidation. In addition, the reaction rate was reduced because of competition between these colored intermediates and main molecules.…”
Section: Operation Time Effectmentioning
confidence: 99%
“…Ultrasound could be considered an alternative method that enables and accelerates to degrade of high organic strength wastewater for the first time combined with photocatalyst and UV irradiation to treat PSWW and this is consistent with work done by Abdelhay et al, (2020) reported that the removal efficiency of COD from PSWW continued to increase during the sonication time (180 min). Çancı and Kılıç (2020) declared that the COD removal rate from rose processing wastewater decreased with increased reaction time due to the formation of colored intermediates as a result of oxidation. In addition, the reaction rate was reduced because of competition between these colored intermediates and main molecules.…”
Section: Operation Time Effectmentioning
confidence: 99%